Letter from the office of Platt & Brother to James Curtis Booth - Platt & Brother (1860)
Office of Platt & Brother writes with a complaint that James Curtis Booth's (1810-1888) assay of Bailey's silver was not correct.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Assaying; Silver--Assaying